2019
DOI: 10.1002/bdr2.1488
|View full text |Cite
|
Sign up to set email alerts
|

The association between prenatal alcohol exposure and protein expression in human placenta

Abstract: Background. The need for earlier recognition of children at risk for neurobehavioral problems associated with prenatal ethanol exposure (PAE) has prompted investigations of biomarkers prognostic for altered fetal development. Here, we examined whether PAE alters the expression of these proteins in human placenta, along with other angiogenesis-related proteins and cytokines in subjects selected from an ENRICH prospective cohort. Methods. PAE was ascertained by screening questionnaires, Time-line Follow-back i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(49 reference statements)
0
13
0
1
Order By: Relevance
“…In vivo experimental studies of ethanol consumption during gestation have revealed that ethanol use diminishes AAH expression (both mRNA and protein levels) and, hence, trophoblast survival, motility and invasion; resulting in distorted vascular remodeling and placentation. 14,44,45 In vitro studies with human trophoblastic cells have revealed that small interfering RNA inhibition of AAH reduced Notch signaling, impairing trophoblastic cell motility, both effects related to altered fetal growth. 46 Our results showed a decrease in AAH protein expression due to IGF-1 deficiency, mainly in the junctional zone, where trophoblast cells are located.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experimental studies of ethanol consumption during gestation have revealed that ethanol use diminishes AAH expression (both mRNA and protein levels) and, hence, trophoblast survival, motility and invasion; resulting in distorted vascular remodeling and placentation. 14,44,45 In vitro studies with human trophoblastic cells have revealed that small interfering RNA inhibition of AAH reduced Notch signaling, impairing trophoblastic cell motility, both effects related to altered fetal growth. 46 Our results showed a decrease in AAH protein expression due to IGF-1 deficiency, mainly in the junctional zone, where trophoblast cells are located.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol treatment decreases VEGF in yolk sac membranes by inhibition of angiogenic genes due to excess of alcohol-induced reactive oxygen species production (Wang et al, 2016). However, diminished placental vascular density after early alcohol exposure significantly decreased KDR expression in placenta at term (Holbrook et al, 2019). In addition, in alcoholinduced hypoxic placenta, the release of anti-angiogenic soluble receptor sFlt-1 (Reyes et al, 2012), is associated with maternal endothelial dysfunction (Roberts and Cooper, 2001;Roberts et al, 2011).…”
Section: Pathophysiologic Mechanisms Involved In Alcohol-associated P...mentioning
confidence: 99%
“…However, chronic and acute ethanol exposure seems to induce eNOS activity in the fetoplacental unit in other model and HUVEC cells, respectively (Acevedo et al, 2001). Anyway, inhibition or stimulation of NO synthesis by alcohol use throughout pregnancy leads to vasoconstriction of the placenta and umbilical vessels and results in hypoxia and reduced fetal malnutrition (Lui et al, 2014;Gundogan et al, 2015;Lo et al, 2017;Holbrook et al, 2019;Ohira et al, 2019). Consequently, the impaired placental function leads to an increase in oxidative stress that compromises placentation as it alters trophoblast cell motility (Kay et al, 2000;Gundogan et al, 2008).…”
Section: Pathophysiologic Mechanisms Involved In Alcohol-associated P...mentioning
confidence: 99%
“…Increased glucocorticoid levels with alcohol consumption ( 25 ) may play a role in reduced blood flow, given known impacts of cortisol on placental angiogenesis ( 26 ). In human placentae from pregnancies in which women were prospectively assessed to have used alcohol, levels of two angiogenic proteins vascular endothelial growth factor receptor 2 (VEGFR2) and annexin-A4 (ANX-A4), were reduced ( 27 ). VEGFR2 and ANX-A4 both enhance proliferation, migration, and survival of the endothelial cells critical for placental blood vessels, suggesting that maternal and/or fetal blood flow that underlies many other placental functions may be dysregulated A trend increase of the pro-inflammatory cytokine, TNFα, in placenta after alcohol exposure also suggests that placental processes sensitive to inflammation, such as serotonin production, may be affected.…”
Section: Fetal Alcohol Spectrum Disordermentioning
confidence: 99%